Development Strategies of Oelsonbai Research Center Scientific Tourism in KHDTK Oelsonbai Kupang - Wieke Herningtyas; Gerson Ndawa Njurumana; Maria Elisabet Saptaria Feriani; Is Mugiono (Jurnal Sylva Lestari, 2022)
Oelsonbai Research Center is one of the management instruments of Forest Area for Specific Purposes (Kawasan Hutan Dengan Tujuan Khusus) Oelsonbai to help promote research and development results bundled in scientific tourism package. The Oelsonbai Research Center development was still new, so this research aimed to determine development strategies of the Oelsonbai Research Center scientific tourism in forest area for specific purposes Oelsonbai. This research was conducted from June to July 2021. The research methods used were interviews using questionnaires on 33 respondents, field observation, in-depth interviews with the administrators, and Strength, Weakness, Opportunities, Threats (SWOT) analysis. The results indicated that Oelsonbai Research Center could develop into a tourism area. Therefore, strategies to develop the Oelsonbai Research Center are proposed in this research. The proposed strategies are: developing the potential of the area with better quality tourism objects, executing the created forest area and scientific tourism attraction planning, increasing socialization and promotion activities with digital media, increasing collaborative relations between researchers and other researchers and academics in education, research and scientific tourism, involving the community in tourism activities by establishing business institutions such as cooperatives and establishing cooperation with other parties in developing the Oelsonbai Research Center scientific tourism. Keywords: Natural tourism, Oelsonbai Research Center, Scientific tourism, SWOT analysis, Tourism